Are there differences in the treatment information received to support guided self-management between asthma and allergy patients?: A community pharmacy survey in Finland - Juha Markus Heikkilä; Paula Bergman; Juha Jantunen; Johanna Salimäki; Paula Kauppi; Marika Pohjanoksa-Mäntylä (Elsevier, 2021)
Background: Guided self-management of asthma supported by health care professionals is a well-established approach. For allergy patients, there is less guidelines and evidence for guided self-management than for asthma patients. Objective: The objective of this study was to find out how commonly asthma and allergy patients receive written action plans, how much and from which sources they receive treatment information to support their self-management, and to identify associated factors that may influence the support of guided self-management, and if there are any differences between these patients. Methods: A nationwide survey was conducted in Finnish community pharmacies (n = 785) in September 2016 targeting patients buying prescription medicines for asthma or allergies. Results: Responses were received from 46% of targeted pharmacies. Around 73% of the asthma patients, 61% of patients at risk of anaphylaxis, and less than 50% of the other allergy patients had received a written action plan. The most common source of treatment information for both patient groups was pharmacists. Allergy patients sought information more from written sources than asthma patients. Older males and patients with lower education received less treatment information. About 10% of both asthma and allergy patients did not report receiving any treatment information. Conclusion: The majority of asthma patients and allergy patients at risk of anaphylaxis had received a written action plan, while fewer than half of other allergy patients had received a written action plan. For both asthma and allergy patients, community pharmacists are the most common source of treatment information. Allergy patients seek more information from written sources than asthma patients. Pharmacists have a crucial role in the support of self-management for these patients.